Sudden Cardiac Death in Young Athletes: Screening and Risk Indicators - Antonio da Silva Menezes Junior (New Frontiers in Medicine and Medical Research Vol. 3, 2021)
Background: Sudden cardiac death (SCD) in athletes during physical activity is rare. Sudden cardiac death (SCD) in a young athlete is a tragic event and is the leading medical cause of death in this population. The precise incidence of SCD in young athletes has been subject of debate, with studies reporting drastically different rates (1:917,000 athlete-years (AYs) to 1:3000 AYs) depending on the methodological design of the investigation or the targeted population. Objectives: To evaluate the warning signs for SCD in young athletes and correlate them with electrocardiographic data. Methods: This was a case-control, prospective study, and comparing athletes with sedentary individuals. The Sudden Cardiac Death Screening of Risk Factors (SCD-SOS) questionnaire was applied, and resting electrocardiography was performed. Results: In total, 898 participants were included, 589 (65.6%) in the case group (athletes) and 309 (34.4%) in the control group (sedentary). Fainting episodes were significantly less frequent in athletes (odds ratio 0.252, p<0.001). Heart rates were not significantly different. The most common electrocardiographic findings were sinus arrhythmia, right bundle branch conduction disorder, and early repolarization. Conclusion: Young athletes had a lower frequency of risk indicators for sudden cardiac death. There was a positive correlation between fainting reported by athletes and the duration of the QRS complex. SCD is the leading cause of death in athletes during exercise and usually results from intrinsic cardiac conditions that are triggered by the physiologic demands of forceful exercise. Up-to-date rates of SCD appear to be at least 4 to 5 times higher than earlier estimated, with men, African Americans, and male basketball players being at greatest risk. Evolving data suggest that the leading finding associated with SCD in athletes is a structurally normal heart (autopsy-negative sudden inexplicable death)